A single-walled carbon nanotube thin film solar microcell with V-groove array structure. (December 2013) - Chang, Yiyang; Liu, Peng; Zhang, Jinwen
This article reports an exploratory single-walled carbon nanotube thin film solar microcell with V-groove array structure on Si (100) substrate. Single-walled carbon nanotube thin film–Si heterojunction serves as energy conversion part in solar microcells, including electron–hole pair generation, carrier collection and transportation. V-groove was designed and prepared on silicon substrate by KOH anisotropic wet-etching for improving the performance of solar microcell. Simple solution–evaporation method was used to achieve conformal single-walled carbon nanotube thin film on V-groove silicon substrate. Under 100 mW/cm 2 solar illumination, our solar microcell with V-groove arrays shows open-circuit voltage (VOC ) of 195 mV, short-circuit current density (JSC ) of 4.76 µA/cm 2 and fill factor of 24.8%. The VOC and JSC are, respectively, enhanced by 387.5% and 217.3% compared to the microcell without V-groove arrays. It is proved that the V-groove structure can improve the performance of single-walled carbon nanotube thin film solar microcell.